A cone-beam computed tomography study of the prevalence and location of the second mesiobuccal root canal in maxillary molars - Seong-Ju Lee; Eun-Hye Lee; Se-Hee Park; Kyung-Mo Cho; Jin-Woo Kim (Restorative Dentistry & Endodontics, 2020)
ObjectivesThis study aimed to investigate the incidence and location of the second mesiobuccal root (MB2) canal in maxillary molars with the aid of various measuring points and lines using cone-beam computed tomography (CT).Materials and MethodsA total of 205 images of patients who underwent cone-beam CT examinations between 2011 and 2015 as part of their dental diagnosis and treatment were included. There were 76 images of the maxillary first molar and 135 images of the maxillary second molar. Canal orifices were detected at −1 mm from the top of the pulpal floor on cone-beam CT images. Image assessment was performed by 2 observers in reformatted image planes using software. Assessments included measurement of the distance between the MB1 and MB2 canals, and the angles between the lines connecting the MB1-MB2 and distobuccal (DB)-palatal (P) canals. The data were analyzed using the student's t-test.ResultsThe prevalence of the MB2 canal was 86.8% in the first molar and 28.9% in the second molar. The angle between the lines connecting the MB1-MB2 and DB-P canals was 2.3° ± 5.7° in the first molar and −3.95° ± 7.73° in the second molar. The distance between the MB1 and MB2 canals was 2.1 ± 0.44 mm in the first molar and 1.98 ± 0.42 mm in the second molar.ConclusionsThe angles between the lines connecting the MB1-MB2 and DB-P canals was almost parallel. These findings may aid in the prediction of the location of the MB2 canal orifice.